Agricultural Policy Environmental eXtender Simulation of Three Adjacent Row‐Crop Watersheds in the Claypan Region. Issue 3 (1st May 2013) - Anomaa Senaviratne, G.M.M.M.; Udawatta, Ranjith P.; Baffaut, Claire; Anderson, Stephen H.
Abstract : The Agricultural Policy Environmental Extender (APEX) model is used to evaluate best management practices on pollutant loading in whole farms or small watersheds. The objectives of this study were to conduct a sensitivity analysis to determine the effect of model parameters on APEX output and use the parameterized, calibrated, and validated model to evaluate long‐term benefits of grass waterways. The APEX model was used to model three (East, Center, and West) adjacent field‐size watersheds with claypan soils under a no‐till corn ( Zea mays L.)/soybean [ Glycine max (L.) Merr.] rotation. Twenty‐seven parameters were sensitive for crop yield, runoff, sediment, nitrogen (dissolved and total), and phosphorous (dissolved and total) simulations. The model was calibrated using measured event‐based data from the Center watershed from 1993 to 1997 and validated with data from the West and East watersheds. Simulated crop yields were within ±13% of the measured yield. The model performance for event‐based runoff was excellent, with calibration and validation r 2 > 0.9 and Nash–Sutcliffe coefficients (NSC) > 0.8, respectively. Sediment and total nitrogen calibration results were satisfactory for larger rainfall events (>50 mm), with r 2 > 0.5 and NSC > 0.4, but validation results remained poor, with NSC between 0.18 and 0.3. Total phosphorous was well calibrated and validated, with r 2 > 0.8 and NSC > 0.7, respectively. The presence of grass waterways reduced annual total phosphorus loadings by 13 to 25%. The replicated study indicates that APEX provides a convenient and efficient tool to evaluate long‐term benefits of conservation practices.